Peramalan Jumlah Permintaan Tepung Terigu pada Bahan Baku Roti Menggunakan Metode Triple Exponential Smoothing Brown di Usaha Roti Anggun - Farhati, Nia Awra; Murni, Dewi (UNIVERSITAS NEGERI PADANG, 2023)
Wheat flour is the main raw material in making bread. The amount of demand for wheat flour at Usaha Roti Anggun comes from distributors which will affect the amount of bread production. The purpose of this study is to form a forecasting model for the amount of demand for wheat flour in bread raw materials at Roti Anggun Business using the Brown type triple exponential smoothing method and forecast the amount of demand for wheat flour based on the model formed. The forecasting method used is Brown's Triple Exponential Smoothing with the parameter α which minimizes the MSE is 0.42. The results of forecasting the total demand for wheat flour at Usaha Roti Anggun with the equation model